\(4x-10-x^2\)
\(=-\left(x^2-4x+10\right)\)
\(=-\left(x^2-4x+4\right)-6\)
\(=-\left(x-2\right)^2-6\)
Vì \(-\left(x-2\right)^2\le0;\forall x\)
\(\Rightarrow-\left(x-2\right)^2-6\le-6< 0;\forall x\)
Vậy \(4x-10-x^2< 0\forall x\)
Đúng 0
Bình luận (0)
Ta có: 4x - 10 - x2
= - ( x2 - 4x +10 )
= - ( x2 - 4x + 4 ) - 6
= - ( x - 2 )2 - 6
Vì - ( x-2 )2 \(\le\)0 với \(\forall x\)
=> - ( x - 2 )2 - 6 < 0 với \(\forall x\)
hay 4x - 10 - x2 < 0 với \(\forall x\)(đpcm)
( Dấu "=" xay ra <=> x= 2 )
Chúc bn học tốt ^^
Đúng 0
Bình luận (0)